IIDENTIFIKASI BENTUK STIGMA YANG DIALAMI OLEH KELUARGA YANG MERAWAT ODGJ DI PAMEKASAN: STUDI QUALITATIF - Holis, Willi; Amir, Faisal; Shiddiq Suryadi, Moh. (JURNAL MEDICAL P-ISSN : 2685-7960 e-ISSN : 2685-7979, 2024)
Stigma towards People with Mental Disorders (ODGJ) is a complex phenomenon that not only affects individuals who experience mental disorders, but also the families who care for them. Families often face various forms of stigma that can have psychological, social, and even economic impacts. The purpose of this study was to identify the forms of stigma experienced by families who care for ODGJ in Pamekasan. This study is a qualitative study, with research subjects of 11 families with ODGJ who experience stigma in their environment. Data were collected through in-depth interviews. The results of this study showed that the forms of stigma experienced by families with ODGJ differ from each other, some experience social rejection and others experience oppression. Stigma towards families with ODGJ appears in various forms; social rejection and oppression. These forms of stigma collectively create an unsupportive environment and often isolate the family.